The most prominent Translators of The Abbasid Era - ABD OUN SHYAA, ASMAA (Journal of College of Education, 2020)
most prominent Translators of The Abbasid Era The Through our study of translation at the time of the Abbasid Caliphs, these translations were Predominated that they were from Greek to Arabic especially in the fields of medicine, philosophy and logic .AS for the translation from Persian to Arabic , medicine did not prevail in it, but subjects of literary heritage overcame it .As for the translation from Hindi to Arabs have known the heritage of India throng translation after the conquests operations . We have translated the work of some of the most prominent translators in the Abbasid era who took over the task of translating Persian , Greek and Indian quotes into Arabic and informing them about the Arabs.